Macroeconomic Performance and Fiscal Policy Adjustments in the Medium Term Alternative Medium-Term Scenarios - Richardson, Pete (OECD Economics Department Working Papers, 1994)
This paper describes a number of alternative medium-term scenarios for the OECD economies and related policy stimulations using the OECD world model INTERLINK. The starting point of the analysis is a reference scenario to 2000 featuring a general recovery of the OECD economies to steady state non-inflationary growth. The paper goes on to examine the implications of slower growth for the paths of fiscal balance and public debt, and the changes in policy mix which might be necessary to restore announced fiscal policy objectives whilst limiting damage to the wider range of policy objectives. A further section goes on to examine the simulated effects of changes of fiscal and monetary policy stance on output, employment, inflation and public debt over the medium term ...